Potential for cell therapy in Parkinson's disease using genetically programmed human embryonic stem cell–derived neural progenitor cells. Issue 12 (7th May 2014) - Ambasudhan, Rajesh; Dolatabadi, Nima; Nutter, Anthony; Masliah, Eliezer; Mckercher, Scott R.; Lipton, Stuart A.
ABSTRACT Neural transplantation is a promising strategy for restoring dopaminergic dysfunction and modifying disease progression in Parkinson's disease (PD). Human embryonic stem cells (hESCs) are a potential resource in this regard because of their ability to provide a virtually limitless supply of homogenous dopaminergic progenitors and neurons of appropriate lineage. The recent advances in developing robust cell culture protocols for directed differentiation of hESCs to near pure populations of ventral mesencephalic (A9‐type) dopaminergic neurons has heightened the prospects for PD cell therapy. Here, we focus our review on current state‐of‐the‐art techniques for harnessing hESC‐based strategies toward development of a stem cell therapeutic for PD. Importantly, we also briefly describe a novel genetic‐programming approach that may address many of the key challenges that remain in the field and that may hasten clinical translation. J. Comp. Neurol. 522:2845–2856, 2014. © 2014 Wiley Periodicals, Inc.